Efek Takaran Pupuk Hayati terhadap Pertumbuhan dan Produksi Caisim (Brassica juncea L.) - Haperidah Nunilahwati; Neni Marlina; Yani Purwanti; Laili Nisfuriah; Ida Aryani; Rosmiah Rosmiah; Zulfakar Zulfakar (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Nunilahwati H, Marlina N, Purwanti Y, Nisfuriah L, Aryani I, Rosmiah R, Zulfakar Z. 2022. Effect of dose of biofertilizer on growth and production of caisim (Brassica juncea L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 226-233. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Biofertilizer are live microorganisms that are mixed into the soil as inoculants to help provide certain nutrients for plants. This study aimed to determine the effect of biofertilizer doses on the growth of mustard greens (Brassica juncea L.). The study was carried out in Seberang Ulu II District, Palembang City, South Sumatra from February to May 2021. The method used was a Non-Factorial Randomized Block Design (RAK) with 6 (six) treatments and 4 (four) replications with treatment H0 = 0 kg/ha, H1 = 20 kg/ha (0.05 g/polybag), H2 = 40 kg/h (0.10 g/polybag), H3 = 60 kg/ha (0.15 g/polybag), H4 = 80 kg/ha (0.20 g/polybag) and H5 = 100 kg/ha (0.25 g/polybag). The results of the diversity analysis showed that the effect of the dose of biofertilizer applied to caisim on plant height (cm), top root weight (g), and bottom root weight (g) had a significant effect, while plant height (cm) and leaf width (cm) had a very significant effect. The application of biofertilizer of 20, 40, 60 kg/ha, and 100 kg/ha on caisim plants showed lower growth and production than the application of 80 kg/ha of biofertilizer. The dose of biofertilizer 80 kg/ha is the best treatment for the growth and production of caisin mustard plants weighing 56.75 g/polybag.